Econometrics and risk management - Fomby, Thomas; Fouque, Jean-Pierre; Solna, Knut (Advances in econometrics ;, 2008)
The main theme of this volume is credit risk and credit derivatives. Recent developments in financial markets show that appropriate modeling and quantification of credit risk is fundamental in the context of modern complex structured financial products. The reader will find several points of view on credit risk when looked at from the perspective of Econometrics and Financial Mathematics. The volume consists of eleven contributions by both practitioners and theoreticians with expertise in financial markets, in general, and econometrics and mathematical finance in particular. The challenge of modeling defaults and their correlations is addressed, and new results on copula, reduced form and structural models, and the top-down approach are presented. After the so-called subprime crisis that hit global markets in the summer of 2007, the volume is very timely and will be useful to researchers in the area of credit risk.